Stakeholder Engagement in Blue Carbon Sector: A Bibliometric Analysis - Muslicha Anisa; Koestoer Raldi Hendro (BIO Web of Conferences)
As part of its commitment to the Paris Agreement and addressing climate change, Indonesia has submitted its first Nationally Determined Contribution (NDC) and is now preparing its Second NDC with more ambitious targets, incorporating a broader focus on the blue carbon sector. Achieving these climate goals requires strengthening stakeholder engagement within the blue carbon sector. This study employs a comprehensive bibliometric analysis, followed by a Systematic Literature Review (SLR), to assess stakeholder engagement in the blue carbon sector and identify relevant knowledge. The findings reveal that only thirteen articles were identified, with a significant concentration of studies from Australia. The research also compares four selected countries— the United States, Australia, the Philippines, and Indonesia— in the context of blue carbon, based on insights extracted from six key articles. The study identifies similarities in both the blue carbon context and the approaches to stakeholder engagement.